Upaya Meningkatkan Literasi Membaca Menggunakan Teknik Bercerita di Sekolah Dasar - Firanty, Rif'ah Meilya; Dayu, Dian Permatasari Kusuma; Mayangsari, Nur (AS-SABIQUN, 2024)
Reading literacy is important for academic success and making informed decisions. However, according to the results of PISA 2022, Indonesia is ranked 69th out of 81 countries in the reading literacy category. Schools have prepared reading corners in each class, but they have not been implemented optimally due to the lack of interest in student literacy. Storytelling techniques can encourage students to actively participate in the learning process by understanding, remembering, and conveying information again. The purpose of this study was to determine how well students understood the contents of the reading and increase their interest in reading literacy through a storytelling approach. With the Kemmis & McTaggart design, this study is a classroom action with four stages: planning, action, observation, and reflection. Data were collected using a questionnaire to determine students' reading literacy interests and a test sheet to measure how far students understood the contents of the reading. The data analysis process used a qualitative approach. The study was conducted in two cycles, namely cycle I and cycle II. The results showed that students who were previously in the low and medium categories were now in the high and very high categories, showing a significant increase in their interest in reading literacy. In addition, reading comprehension also increased, as evidenced by the results of the reading comprehension test from cycle I to cycle II showing a significant increase. Storytelling techniques in learning can be said to be effective in attracting students' reading literacy interest and deepening their understanding of the contents of the reading.